Risk factors for postoperative complications after total laryngectomy following radiotherapy or chemoradiation: a 10‐year retrospective longitudinal study in Eastern Denmark. (December 2015) - Wulff, N.B.; Kristensen, C.A.; Andersen, E.; Charabi, B.; Sørensen, C.H.; Homøe, P.
Abstract : Objectives: To determine the rates of and risk factors for postoperative complications following total laryngectomy in patients treated with radiotherapy or chemoradiation. Design: Retrospective longitudinal study. Setting: Tertiary medical centres. Participants: A total of 143 patients undergoing total laryngectomy for squamous cell carcinoma of the larynx or hypopharynx. Main outcome measures: Overall postoperative complications and fistula formation. Results: Overall postoperative complications, fistula formation, wound infection, bleeding and wound necrosis within one year after total laryngectomy occurred in 56.6%, 42.3%, 31.0%, 11.3% and 9.2% of patients, respectively. Stenosis of the pharynx/oesophagus and stoma shrinkage within five years after surgery were each seen in 18.2% of cases. In 66.7% of cases, conservative treatment of the fistulas was chosen. Rehospitalisations within five years occurred for 44.8% with a median rate of 1.5 (range 1–11). Smoking status ( P  = 0.005 and 0.013) and chronic obstructive pulmonary disease (COPD) ( P  = 0.013 and 0.011) were significant risk factors for both overall postoperative complications and fistula formation in uni‐ and multivariate analysis. Tumour localisation in the hypopharynx was associated with overall postoperative complications ( P  = 0.036). Residual tumour or cancer recurrence was associated with late‐onset fistulas ( P  < 0.001). Conclusion: The frequencies of postoperative complications after total laryngectomy were comparable with similar international studies, although fistula formation rate is increasing in Denmark. We suggest optimising treatment of COPD and to further encourage to smoking cessation. We propose that development of fistulas >2 months after surgery prompts immediate biopsies. Additionally, we suggest standardised registration of surgical techniques to identify variables affecting the frequency of postoperative complications.